Mental Health Problems Associated with Asylum Procedures of Refugees in European Countries - Womersley, Gail; Kloetzer, Laure; Goguikian Ratcliff, Betty (My University, 2017)
Events that took place before migration have an influence on the mental health of asylum seekers and refugees. But research findings show that the majority of stress factors are directly related to post-migration living conditions and restrictions. Prolonged legal insecurity, the obligation to move from one center to another, and isolation among other factors contribute to the deterioration of refugees’ mental health. Implications reach far beyond the individual: it is a question of social and economic significance for Switzerland as well.
Keywords: Asylum; mental health; trauma